Sequence analysis of the hepatitis C virus genome recovered from serum, liver, and peripheral blood mononuclear cells of infected chimpanzees. - Shimizu, Y K (1997)
Of 13 different strains of hepatitis C virus (HCV) in the inoculum used, only 1 persisted in human lymphocyte cell lines infected in vitro (N. Nakajima, M. Hijikata, H. Yoshikura, and Y. K. Shimizu, J. Virol. 70:3325-3329, 1996). To determine whether that particular strain (designated H1-2) has a tropism for lymphocytes in vivo, we sequenced hypervariable region 1 (HVR1) of the genome of HCV recovered from the sera, livers, and peripheral blood mononuclear cells (PBMC) of chimpanzees infected with plasma H77, the same inoculum used for the in vitro studies. In the PBMC collected from two chimpanzees during the early phase of infection, H1-2 was detected as the only or predominant HVR1 sequence. H1-2 was also detected in PBMC obtained during persistent infection from a chimpanzee that had been treated with immunosuppressants. From the livers of these chimpanzees, two to six different strains were recovered but H1-2 was not detected. Thus, H1-2 appeared to have an affinity for lymphocytes not only in vitro but also in vivo. In samples collected from a chimpanzee after 6 years of infection, however, such tissue compartmentalization of the HCV genome was not observed; a single strain became predominant in the serum, liver, and PBMC. An HCV strain capable of replicating in both the liver and PBMC probably emerged during in vivo replication and persisted.